Harmonization of Mineral and Coal Mining Licensing Regulations in the National Legal System - Tinambunan, Hezron Sabar Rotua (PT. Anagata Sembagi Education, 2026)
Harmonization of mineral and coal mining (minerba) licensing regulations is a crucial issue in the national legal system, particularly following the amendment to the Minerba Law and its integration into the Job Creation Law regime. These regulatory dynamics have raised issues of norm synchronization, both vertically and horizontally, which impact legal certainty and natural resource governance. This study aims to analyze the normative construction of mineral and coal licensing within the regulatory hierarchy, identify forms of norm conflict, and formulate the urgency of regulatory harmonization from a rule of law perspective. This study uses a normative juridical method with a statute approach, a conceptual approach, and a legal system approach. Primary legal materials include the 1945 Constitution, the Minerba Law, the Job Creation Law, the Regional Government Law, and environmental and spatial planning regulations, which are analyzed prescriptively. The results show norm conflict in the form of central-regional authority conflicts, disharmony between mining business permits and environmental approvals, and overlaps between WIUPs and land rights. This situation undermines the principle of legal certainty (rechtssicherheit), potentially violating the principles of utility and justice, and weakening the legitimacy of state administrative actions. Harmonizing regulations through legislative review, strengthening norm synchronization mechanisms, and consistently applying the principles of lex superior, lex specialis, and lex posterior are prerequisites for realizing equitable and sustainable mining governance.